Draft Annual Plan 2002-03 State Planning commission Tamil Nadu - Planning Commission (Planning Commission, 2002)
The estimated production for these two crops in 2001-02 are 16.00 and 6.50 lakh tonnes respectively. The area under paddy which was at 21.64 lakh ha. in 1999-00 declined to 21.13 lakh hectares (2.3%) in 2000-01. However, the area under foodgrains increased from 36.33 lakh hectares in 1999- 2000 to 42.99 lakh hectares (18.3%) in 2000-01. The area under all other crops showed an increasing trend in 2000-01. The oilseed production increased by 12.6 per cent from 14.07 lakh tonnes in 1999-00 to 15.84 lakh tonnes in 2000-01 and the projected outturn was at 22.80 lakh tonnes during 2001-02. However, the production of cotton and sugarcane experienced a decline in 2000-01. The production of these crops declined from 3.40 and 34.29 lakh tonnes in 1999-00 to 3.26 and 33.57 lakh tonnes in 2000-01, respectively.
Draft Annual Plan 2002-03
Government of Tamil Nadu